Food safety in China : a comprehensive review - Wu, Linhai; Zhu, Dian. (Boca Raton : Taylor & Francis, 2015)
'This book provides a comprehensive review of the efforts put forth by China to prevent food safety concerns, including the abuse of food additives. Looking at food producers and operators, consumers, and government agencies as part of an organic system, the book examines the complete system of the food supply chain from multi-scientific systematic points of view. It begins with the production of agricultural products and investigates the changing track of food safety (including imported and exported products) in the key aspects of production, circulation, and consumption between 2006 and 2011'--
Includes bibliographical references (pages 315-328) and index.
Keywords: Food adulteration and inspection -- China; Food -- Safety measures -- Government policy -- China; Food contamination -- China